Keragaman Qiraat dalam Mushaf Kuno Nusantara - Mustopa, Mustopa (Lajnah Pentashihan Mushaf Al-Qur'an, 2014)
The majority of the Muslims in Indonesia almost know only one style of qiraat (the Art of reciting the Quran) namely Nafi Ã¢â‚¬Ëœan Ã¢â‚¬ËœAsim qiraat. This writing wants to explain that, historically, the Nusantara Ulama in the past had written and introduced other sytle of qiraat to some ancient Nusantara Mushafs. One of the Mushaf is the Mushaf of the Sultan of Ternate. This Mushaf uses qiraat namely QÃ„ÂlÃ…Â«n Ã¢â‚¬Ëœan NÃ„Âfi. This identification is explained by making the comparison of some words which become spot of difference between the qiraat of Hafs Ã¢â‚¬Ëœan Ã¢â‚¬ËœAsim and that of QÃ„ÂlÃ…Â«n Ã¢â‚¬Ëœan NÃ„ÂfiÃ¢â‚¬Ëœ. Although there are some lacks of the writings, however, in general, it can be said that the of the Mushaf of Sultan of Ternate uses the qiraat of QÃ„ÂlÃ…Â«n Ã¢â‚¬Ëœan NÃ„ÂfiÃ¢â‚¬Ëœ. Keyword: Qiraat, Quran manuscript, Hafs Ã¢â‚¬Ëœan Ã¢â‚¬ËœAsim, QÃ„ÂlÃ…Â«n Ã¢â‚¬Ëœan NÃ„ÂfiÃ¢â‚¬Ëœ, The Sultan of Ternate